Khan Academy as Supplemental Instruction: A Controlled Study of a Computer-Based Mathematics Intervention - Kelly, Daniel Patrick; Rutherford, Teomara (International Review of Research in Open and Distributed Learning, 2017)
Khan Academy is a large and popular open educational resource (OER) with little empirical study into its impact on student achievement in mathematics when used in schools. In this study, we examined the use of Khan Academy as a mathematics intervention among seventh grade students over a 4-week period versus a control group. We also compared differences between students who had supplemental mathematics instruction and those who had not. In both cases, we found no statistically significant differences in student test scores. Khan Academy has several internal metrics used to track student performance and use. We found significant relationships between these metrics and student test scores in this study. Khan Academy and other OER provide access to information and knowledge to large numbers of the population. This research adds to the discourse methods by which Khan Academy and other OER may affect learners.